Implementation of Anti-Stroke Exercises to Address Stroke Prevention in Villages - Erawati, Erna; Ridwan, Moh.; Triredjeki, Hermani; Talib, Susi Tentrem Roestyati; Hastuti, Tulus Puji (Jurnal Kesehatan, 2025)
Stroke remains a leading cause of disability and death, particularly in village areas where access to health education and preventive services is limited. While physical activity is known to reduce stroke risk, structured, community-based prevention programs are rarely implemented or studied in village settings. This study evaluates the implementation of anti-stroke exercises for stroke prevention in a village in Magelang, Central Java. A qualitative descriptive approach was used. Data were collected through focus group discussions and semi-structured interviews with village residents, community health workers, and local leaders in three village villages where the anti-stroke exercise program had been introduced. Thematic analysis was used to interpret the data. Participants reported increased awareness of stroke risk factors and the importance of physical activity. The exercise sessions were generally well-received and promoted social interaction among participants. Three key points for implementing anti-stroke exercises in rural areas aimed at preventing stroke were identified: early detection, education, and community participation. The program contributed to stroke prevention efforts by raising awareness and encouraging healthier lifestyles in village communities. Community engagement and leadership played crucial roles in the success of implementation. To strengthen the program, ongoing facilitator training, integration into broader public health strategies, and government support are needed. Regular monitoring and community feedback can help sustain and scale the initiative effectively.